Risiko Impfen? - Kowalzik, Frank; Zepp, Fred (DMW - Deutsche Medizinische Wochenschrift, 2019)
Skepticism about vaccination is not new, but the perception of vaccine-related risks has changed in recent decades. In addition to aspects such as knowledge about vaccines, trust in medical care structures and political institutions, socio-economic, cultural and religious views also play an important role. These factors differ significantly worldwide and regionally. In almost all surveys, confidence in vaccines and/or the healthcare system is identified as essential for a positive vaccination decision. Confidence in vaccines correlates with the assessment of the specific individual disease risk and the potential side effects of the vaccines. Subjective perception of risk seldom corresponds to objectively measurable facts. Rather, it is distorted by individual perception in both directions (underestimation and overestimation). Transparent, science-based communication is helpful in promoting and maintaining trust in healthcare. Pediatricians and family physicians are the most important confidants for parents on questions about health care and vaccination recommendations.
Keywords: Impfskepsis; Pflichtimpfung; Vertrauen; Risikowahrnehmung; Unterschätzung